Information-Driven Design as a Potential Approach for 3D Printing of Skeletal Muscle Biomimetic Scaffolds - Baiguera, Silvia (Nanomaterials (Basel), 2020)
Severe muscle injuries are a real clinical issue that still needs to be successfully addressed. Tissue engineering can represent a potential approach for this aim, but effective healing solutions have not been developed yet. In this regard, novel experimental protocols tailored to a biomimetic approach can thus be defined by properly systematizing the findings acquired so far in the biomaterials and scaffold manufacturing fields. In order to plan a more comprehensive strategy, the extracellular matrix (ECM), with its properties stimulating neomyogenesis and vascularization, should be considered as a valuable biomaterial to be used to fabricate the tissue-specific three-dimensional structure of interest. The skeletal muscle decellularized ECM can be processed and printed, e.g., by means of stereolithography, to prepare bioactive and biomimetic 3D scaffolds, including both biochemical and topographical features specifically oriented to skeletal muscle regenerative applications. This paper aims to focus on the skeletal muscle tissue engineering sector, suggesting a possible approach to develop instructive scaffolds for a guided healing process.